Contemporary Britain - McCormick, John, 1954- (London ; New York : Bloomsbury Academic, 2023)
"A thought-provoking and jargon-free introduction to British politics, society, culture and geography. Filled with topical case studies, the latest empirical data and analysis, this new edition shows readers how and why Britain has become the country that it is today"--
The emergence of Britain -- Industrialization and empire -- World War II and its consequences -- Change and discontent -- From Thatcher to Blair -- The four crises and beyond -- Geography and climate -- Natural resources -- The environment -- The people of Britain -- Nationalism and regionalism -- Immigration and race -- Social class -- The changing family -- Social services and healthcare -- Education -- Law and order -- Understanding British government -- The constitution -- The monarchy -- Prime Minister and Cabinet -- Parliament -- The judiciary -- The bureaucracy -- Regional and local government -- Political culture -- Elections and referendums -- Political parties -- Interest groups -- The media -- Understanding the British economy -- From hands-off to hands-on, and back again -- The changing economic landscape -- Trade and foreign investment -- The economic implications of Brexit -- Understanding British culture -- The changing national identity of Britain -- The arts -- Sports and leisure -- Religion -- The changing British global role -- The Commonwealth -- The Atlantic Alliance -- Britain and Europe -- The changing role of the British military.
Includes bibliographical references (pages 216-224) and index.
Keywords: Great Britain -- Description and travel